Sosialisasi Kesiapsiagaan dalam Menghadapi Bencana Gempa Bumi - Melani Kartika Sari; Pria Wahyu Romadhon Girianto (Prosiding SPIKesNas : Seminar Publikasi Ilmiah Kesehatan Nasional, 2023)
Earthquake is one of the disasters that often occurs in Indonesia. Earthquakes can cause death, damage to infrastructure and other losses. Dissemination of preparedness in the face of earthquake disaster aims to reduce the risk of falling a lot of casualties. The purpose of socializing preparedness in dealing with earthquake disasters to Palapa Vocational High School students is to provide knowledge about how to take disaster response actions if an earthquake occurs. The number of respondents who were involved in this community service activity was as many as 30 Palam Vocational High School students who were members of a scout organization. After carrying out this community service activity, an increase in student knowledge regarding preparedness in dealing with earthquake disasters was obtained. This can be seen from the average pre-test score of 76, while the average post-test score is 89. Preparedness education needs to be taught in schools and communities so that all elements of society can understand how to deal with earthquakes that can occur at any time. and anywhere. Keywords: Community service, sosialization, preparedness, earthquake